Recombinant Marek’s disease virus expressing VP1 and VP2 proteins provides robust immune protection against chicken infectious anemia virus - Ge, Chengfei; Lu, Hangqiong; Han, Jinze; Sun, Guorong; Li, Shihao; Lan, Xingge; Liu, Yongzhen; Yu, Mengmeng; Hu, Xinyun; Hu, Mingxue; Qi, Xiaole; Cui, Hongyu; et al. (Frontiers in Microbiology, 2025)
Chicken infectious anemia (CIA) is a highly contagious disease caused by the chicken infectious anemia virus (CIAV), and it poses a serious threat to the poultry industry. However, effective control measures and strategies have not been identified. In this study, a recombinant Marek’s disease virus (rMDV) expressing the VP1 and VP2 proteins of CIAV was successfully constructed using CRISPR/Cas9, and a commercial Marek’s disease virus (MDV) vaccine strain was used as the vector. VP1 and VP2 expression by rMDV was confirmed by immunofluorescence assay and western blot analysis, which revealed robust in vitro expression. Further analysis showed that the VP1 and VP2 genes integrated into the MDV genome did not alter the growth kinetics of the virus and remained stable even after 20 passages, indicating the genetic stability of the recombinant virus. In animal studies, vaccination of one-day-old specific-pathogen-free chickens with rMDV induced high levels of CIAV-specific antibodies (1 × 105) and neutralizing antibodies (1:25) and a potent cellular immune response. Moreover, rMDV vaccination conferred an 85% protective index against challenge with a highly virulent strain of CIAV, significantly reducing the occurrence of anemia and thymic atrophy caused by CIAV infection and dramatically suppressing CIAV replication in the thymus. Collectively, these results highlight the potential of rMDV as a vaccine candidate for preventing and controlling CIAV infection, thus offering a new avenue for mitigating the impact of CIA on the poultry industry.